2019
DOI: 10.1007/s13197-019-04065-1
|View full text |Cite
|
Sign up to set email alerts
|

The formulation optimization and properties of novel oleuropein-loaded nanocarriers

Abstract: The present study sought to encapsulate oleuropein as a nutraceutical compound in order to investigate its physical properties and stability. We extracted the phenolic compounds of virgin olive leaf by ethanol-water and acetone-water solvents. The purity of this extract was confirmed by analytical high-performance liquid chromatography using oleuropein standard. Oleuropein was encapsulated with different components (lecithin, linoleic acid, glycerol monostearate, soybean oil, and Tween 80), and the effect of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…As summarized in Table 1, it seemed that the higher the olive oil content, the smaller the particle size, which was then confirmed by TEM micrographs (see Supplementary Materials). These results were in line with other authors, who also reported a decrease in the particle size of NLCs when the liquid lipid amount was increased [52][53][54]. Nevertheless, all formulations displayed adequate sizes between 100 and 200 nm.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…As summarized in Table 1, it seemed that the higher the olive oil content, the smaller the particle size, which was then confirmed by TEM micrographs (see Supplementary Materials). These results were in line with other authors, who also reported a decrease in the particle size of NLCs when the liquid lipid amount was increased [52][53][54]. Nevertheless, all formulations displayed adequate sizes between 100 and 200 nm.…”
Section: Resultssupporting
confidence: 93%
“…In light of the characterization results, NLC-OLE50 seemed to be a promising carrier for OLE with enhanced antioxidant activity and thus we continued to study its efficacy in lung epithelial cell models. Several authors have reported micro-and nanoencapsulation methods for olive leaf extracts but to the best of our knowledge, there is a lack of studies regarding the impact that the formulation process could have on the bioactivity of this polyphenol in a biological system [22,23,52].…”
Section: Cell Experimentsmentioning
confidence: 99%
“…The PDI generally varied from 0 to 1.0; however, an excess of 0.5 represented the wide size distribution and the presence of larger particles and aggregations. 35 As shown in Fig. 1A, the PDI value of WPI-coated liposomes ranged from 0.26 to 0.38, and the PDI increased to around 0.38 to achieve a maximum value at a WPI concentration of 20%.…”
Section: Physical Properties Of Liposomes Coated With and Without The...mentioning
confidence: 76%
“…Oleuropein NLS [41][42][43][44][45] CS NPs [46,47] Hydroxytyrosol Liposomes [43,44,48] CS NPs [26,[49][50][51] PLGA-co-PAA NPs [52,53] Wine Resveratrol Zein-SHA and zein-CS NPs [54,55] mPEG-PLA NPs [56] Nuts Ellagic acid polymeric NPs [57][58][59] TPGS micelles [60] Catechin PLGA NPs [61] CS NPs [62,63] Oregano and basil…”
Section: Olive Oilmentioning
confidence: 99%